2022
DOI: 10.1101/lm.053596.122
|View full text |Cite
|
Sign up to set email alerts
|

Spatial anxiety and self-confidence mediate sex/gender differences in mental rotation

Abstract: A recent meta-synthesis study with a sample of >12 million participants revealed that the male advantage in mental rotation (MR) is the largest cognitive sex/gender difference found in psychological literature. MR requires test takers to mentally rotate three-dimensional cubic figures under time restrictions. Previous studies have investigated how biological and social factors contribute to cognitive sex/gender differences in tasks of this type. Spatial anxiety and self-confidence in MR tasks have received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 60 publications
1
11
1
Order By: Relevance
“…A recent study showed that the correlation between testosterone levels and mental-rotation performance is already evident in infants 5–6 months of age ( Constantinescu et al, 2018 ). On the other hand, several studies have recently proposed that spatial anxiety and self-expectations in performance may also be important factors behind male superiority in mental-rotation tests ( Moè, 2009 ; Alvarez-Vargas et al, 2020 ; Arrighi and Hausmann, 2022 ). Both characteristics can be exacerbated by social situational threats and gender-stereotyping still prevalent in modern societies ( Lauer et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the correlation between testosterone levels and mental-rotation performance is already evident in infants 5–6 months of age ( Constantinescu et al, 2018 ). On the other hand, several studies have recently proposed that spatial anxiety and self-expectations in performance may also be important factors behind male superiority in mental-rotation tests ( Moè, 2009 ; Alvarez-Vargas et al, 2020 ; Arrighi and Hausmann, 2022 ). Both characteristics can be exacerbated by social situational threats and gender-stereotyping still prevalent in modern societies ( Lauer et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current study examined whether affective factors, like confidence in one’s own spatial abilities and spatial anxiety explain individual differences in two types of dissociable spatial abilities, mental rotation and perspective-taking/spatial orientation (Jansen, 2009 ). Recent research has demonstrated a potential role for these two affective factors in explaining individual differences in mental rotation ability (e.g., Alvarez-Vargas et al, 2020 ; Arrighi & Hausmann, 2022 ; Cooke-Simpson & Voyer, 2007 ; Estes & Felker, 2012 ; Lawton, 1994 ; Lyons et al, 2018 ). Less is known about potential links in affective factors and perspective-taking/spatial orientation (though see Lawton, 1994 and Lyons et al, 2018 ) and few studies have attempted to combine both affective factors into one study to examine their roles in predicting different types of spatial abilities (but see Arrighi & Hausmann, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated a potential role for these two affective factors in explaining individual differences in mental rotation ability (e.g., Alvarez-Vargas et al, 2020 ; Arrighi & Hausmann, 2022 ; Cooke-Simpson & Voyer, 2007 ; Estes & Felker, 2012 ; Lawton, 1994 ; Lyons et al, 2018 ). Less is known about potential links in affective factors and perspective-taking/spatial orientation (though see Lawton, 1994 and Lyons et al, 2018 ) and few studies have attempted to combine both affective factors into one study to examine their roles in predicting different types of spatial abilities (but see Arrighi & Hausmann, 2022 ). Should we find a role for affective factors like confidence and spatial anxiety predict individual differences in two types of spatial abilities, this might offer a new promising route to improving spatial ability in intervention studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations